Goal Pursuit in Organizational Health Interventions: The Role of Team Climate, Outcome Expectancy, and Implementation Intentions - Lehmann, Anja I.; Brauchli, Rebecca; Bauer, Georg F. (Frontiers in Psychology, 2019)
In taking a goal pursuit perspective into account, the present study examined associations between the context, process and outcome evaluation of an organizational health intervention (OHI) implemented within 29 teams in a hospital setting. In doing so, team climate for innovation as a context factor was measured at baseline (N = 529). Four to six weeks after baseline, N = 250 team representatives participated in a four-day workshop. During the workshop employees formulated collective goals as action plans to be implemented in the nursing wards. Goal pursuit as a process factor was differentiated into (a) a motivational “goal setting” and (b) a volitional “goal striving” phase. The scale of outcome expectancy (measured after the fourth day of the workshop) was used as an indicator for the goal setting phase. For the operationalization of the goal striving phase, action plans were coded with regard to the proportion of formulated implementation intentions (“if-then plans”). After six months, the outcome of the intervention was measured on a retrospective impact scale (N = 385). The results of the multiple regression analysis and of the multilevel analysis show that both team climate and goal pursuit (outcome expectancy and the proportion of if-then plans) were positively related to the perceived impact of the intervention. Furthermore, the results show that the relationship between team climate and the impact of the intervention was mediated by outcome expectancy. The results highlight the contribution of goal theory within context-process-outcome research that leads to a better understanding of when and why OHIs are effective.